Cytokines in milk and the role of TGF-beta. Issue 1 (January 2018) - Brenmoehl, Julia; Ohde, Daniela; Wirthgen, Elisa; Hoeflich, Andreas
Abstract : Cytokines are required for normal growth and development of the mammary gland and TGF-β prominently represents an established effector of apoptosis, e.g., during involution of the mammary gland. By the control of intracellular signaling pathways, including JAK/STAT, MAPK, PI-3K, and NF-κB, cytokines efficiently regulate cell proliferation and inflammation in the breast. Therefore, cytokines are discussed also in a context of malignant mammary growth. As a group of tissue hormones produced by somatic cells or by cells from the immune system, cytokines are defined by their immunomodulatory potential. Over the past 40 years, multiple cytokines were identified in colostrum and milk. Importantly, cytokines derived from mammary secretions after birth are required for maturation of the immune system in the developing gastrointestinal tract from the suckling. Moreover, recent studies have further assessed the particular interactions between probiotic bacterial strains and cytokines. In light of the increasing prevalence of inflammatory diseases of the gastrointestinal system, the effects of probiotic microorganisms during milk fermentation may have immunotherapeutic potential in the future.